2012
DOI: 10.1136/bmj.e6564
|View full text |Cite
|
Sign up to set email alerts
|

Safe exclusion of pulmonary embolism using the Wells rule and qualitative D-dimer testing in primary care: prospective cohort study

Abstract: Objective To validate the use of the Wells clinical decision rule combined with a point of care D-dimer test to safely exclude pulmonary embolism in primary care.Design Prospective cohort study. Setting Primary care across three different regions of the Netherlands (Amsterdam, Maastricht, and Utrecht).Participants 598 adults with suspected pulmonary embolism in primary care.Interventions Doctors scored patients according to the seven variables of the Wells rule and carried out a qualitative point of care D-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
1
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 22 publications
1
106
1
14
Order By: Relevance
“…They concluded that patients with high Wells score (>4), or low Wells score (≤4) but positive D-dimer test should undergo CTPA. In such cases, a negative CTPA was shown to safely exclude PE, with a low incidence of DVT (0.6%), nonfatal PE (0.2%), and fatal PE (42)(43)(44). Of note, among patients with a high pretest probability for PE but normal D-dimer, the CTPA showed PE in 19%-28% of patients when using quantitative rapid ELISA technique for determining D-dimers or even 24%-36% when using a semiquantitative latex agglutination technique (45,46).…”
Section: Main Pointsmentioning
confidence: 99%
“…They concluded that patients with high Wells score (>4), or low Wells score (≤4) but positive D-dimer test should undergo CTPA. In such cases, a negative CTPA was shown to safely exclude PE, with a low incidence of DVT (0.6%), nonfatal PE (0.2%), and fatal PE (42)(43)(44). Of note, among patients with a high pretest probability for PE but normal D-dimer, the CTPA showed PE in 19%-28% of patients when using quantitative rapid ELISA technique for determining D-dimers or even 24%-36% when using a semiquantitative latex agglutination technique (45,46).…”
Section: Main Pointsmentioning
confidence: 99%
“…La medición de marcadores de laboratorio como el dímero D de alta sensibilidad se recomienda para pacientes con baja probabilidad de TEP en las escalas de validación clínica con sensibilidad de 85% y valor predictivo negativo de 99% (65)(66)(67)(68)(69)(70) .…”
Section: Diagnóstico Embolismo Pulmonarunclassified
“…В связи с этим предложены различные комбинации клинической оценки, измерения D димера плазмы крови и визуа лизационных методов диагностики. Эти алгоритмы были апробированы у больных с подозрением на ТЭЛА, обратившихся за неотложной помощью [99,113,114,116,197] либо госпитализированных по то му же поводу, и совсем недавно -в условиях первич ной медицинской помощи [118,126]. При недостат ке доказательной базы для отмены антикоагулянтов значительно возросло число эпизодов ВТЭ и внезап ных кардиологических смертей в течение 3 мес.…”
Section: диагностическая стратегияunclassified
“…При помощи данных методов в исследованиях безопасно исключается ТЭЛА у больных с низкой клинической вероятностью этого заболевания [99,100,105], однако у больных со средней клинической вероятностью безопасность исключения ТЭЛА с по мощью этих методов не изучалась. Использование данных тестов «у постели больного» обладает уме ренной чувствительностью, но соответствующих клинических исследований не проводилось за ис ключением недавнего исследования в первичном звене медицинской помощи, в котором использова но упрощенное измерение D димера [118], а 3 ме сячный тромбоэмболический риск у больных с ма ловероятным диагнозом ТЭЛА и отрицательным D димером составил 1,5 %.Специфичность D димера при подозрении на ТЭЛА у больных старше 80 лет снижается примерно до 10 % [119]. Недавно получены доказательства о не обходимости коррекции порогового значения D ди мера соответственно возрасту больного [120,121].…”
unclassified